Enhancing English Communication Skills Through Palliative Contexts for Secondary Students - Linauli Happy Christina Zega; Elyin A K Lumban Gaol; Catherine Hermawan Salim (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This activity aims to improve the English speaking skills of tenth-grade students through the implementation of role play activities in a palliative context through Classroom Action Research (CAR). The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects were 32 students of SMAN 19 Jakarta. Data were collected through speaking tests and classroom observations. The speaking test assessed aspects of fluency, accuracy, vocabulary, pronunciation, and pragmatic appropriateness, while the classroom observations documented student participation, engagement, and their responses during the role play activities. The results in Cycle I showed that 46.87% of students achieved the “Good” category, while 53.13% were in the “Fair” category, with an average score of 49.35. The observation results showed moderate student engagement, with 62.50–78.13% of students showing positive behaviors such as active participation, attention, and willingness to use English in the role play. However, some students were still hesitant with a negative percentage of 25–37.50%. Improvement was seen in Cycle II. The proportion of students achieving the “Good” category increased significantly to 84.37%, while only 15.63% remained in the “Sufficient” category. No students fell into the “Poor” or “Very Poor” categories. Observations also confirmed stronger engagement, with over 87% of students demonstrating positive behaviors, including enthusiasm, active discussion, and confidence in using English. It can be concluded that the integration of role play with a palliative context effectively improved students’ English speaking skills and participation in class. Suggestions for repeated improvement were found to improve both linguistic competence and students’ communicative confidence.